Analisis Pemahaman Mahasiswa terhadap Konsep Segitiga pada Geometri euclid melalui Soal Etnomatematika Berbasis Budaya Lokal - Indah Ayu Ramadany; Nabila Azuhra; Nofa Nasywa Ramadhani; Syifa Eriza Nasution; KMA Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Euclidean geometry is a branch of mathematics that examines the properties of plane and spatial figures based on axioms and deductive reasoning. Therefore, understanding the concept of triangles is an important foundation for developing spatial abilities and problem-solving. Euclidean geometry examines the properties of plane and spatial figures through axioms and logical reasoning. Understanding the concept of triangles is crucial for spatial abilities and problem-solving. However, students still tend to memorize formulas without understanding their real-life applications. Therefore, culturally based questions such as traditional houses, ulos cloth, and traditional activities are used to assess conceptual understanding.This study applied a qualitative descriptive method involving 20 Mathematics Education students. Data were collected through an online ethnomathematics-based questionnaire and analyzed using Newman’s error analysis stages. The results showed that the highest errors occurred in understanding questions and writing final answers. Students also had difficulties transforming contextual problems into mathematical models. These findings indicate that the ethnomathematics approach provides more meaningful learning contexts, but students’ conceptual understanding still needs improvement through learning strategies that emphasize reasoning and mathematical communication.